About Methods used During Teaching Reading in Language Lessons - Sattorova Marifat Ortikovna (Research Parks Publishing LLC, 2022)
The systematization of various types of texts is necessary for teaching foreign language communication in order to develop the ability of students to use various genres, tactics and techniques of speech communication. This article examines the stages of reading, analysis of the lexical and grammatical difficulties of the text, the activation of new lexical material and the control of understanding the information contained in the text.